TENAGA KEPENDIDIKAN DALAM PENEMPATAN DAN PEMBINAAN GURU - Marwah Lama’atushabakh; Suklani Suklani (Cross-border, 2023)
However simple the civilization of a society, an educational process occurs or takes place in it. That's why it is often stated that education has existed throughout human civilization. Education makes human resources more quickly understand and be ready to face changes in the work environment. Therefore it is not surprising that a country with a population with a high level of education will have a rapid rate of economic growth. Awareness of the importance of quality education is determined by the role of teachers, school principals, inspectors/supervisors and other supervisors, including parents and the community. The role of education implementers in the field is very important in planning programs, implementing programs, discussing problems encountered, developing and disseminating new ideas and developing teaching materials and teaching and learning aids in schools. In this case the teacher is required to master the field of work in a professional manner. Teacher professionalism will appear if the teacher masters and is able to apply methodological principles in the teaching and learning process.